Nutritional composition, antioxidant, and sensory characteristics of gluten-free biscuits produced from malted finger millet (Eleusine coracana) flours - Kundai Thelma Murungweni; Shonisani Eugenia Ramashia; Mpho Edward Mashau (Discover Food)
Abstract Finger millet (Eleusine coracana) is a gluten-free and nutrient-rich cereal grain which has been recognised for its prospective health benefits. To promote the use of finger millet (FM), the impact of malting on the nutritional content, antioxidant, and sensory characteristics of light and dark brown FM biscuits was evaluated. The two varieties of FM grains were germinated for 0, 24, 48, and 72 h and kilned for 8 h at 30 °C. Malting time significantly increased the ash, fibre, protein and carbohydrate contents of FM biscuits while fat content decreased. Furthermore, malting increased the majority of the macro and micro minerals, polyphenols and antioxidant activity of light and dark brown FM biscuits. In terms of colour, malting time significantly decreased the L* values of both FM biscuits, while low a* and chroma values were only observed in light brown biscuits. Weight, diameter, thickness, and spread ratio significantly decreased (p < 0.05) with increased malting time in both FM biscuits. The hardness of the biscuits increased with the malting period with values varying from 762.53 to 1720.28 g (light brown) and 747.50 to 1918.71 g (dark brown). The panelists preferred gluten-free 24 h malted FM biscuits because they exhibited superior sensory attributes. Malted FM flour (up to 72 h) can be used to prepare nutritious, antioxidant-rich, and healthier gluten-free bakery products such as biscuits.